SEEING RECOUNT FROM SYSTEMIC FUNCTIONAL LINGUISTIC PERSPECTIVE: SINE QUA NON ATTRIBUTES - Rialita Kusuma Shinta Dewi; Eri Kurniawan (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
It is believed that traditional grammar is no longer appropriate to teach students especially in developing their writing skill. Systemic Functional Linguistic (SFL) which focuses on meaning and function behind language is now seen to be well-implemented. The study tried to analyse studentâ€™s piece of writing on one type of text in which Hotel Industry students as the sample of the study should master known as recount text. Purposive type of sampling was chosen since there was only one text analysed which was seen as the most problematic one. Content analysis as the implementation of qualitative research was chosen as the design of the study. The findings showed that the major problem student encountered mostly on grammatical structures in which there were found some errors on it. Regarding the three metafunctions, it was known that the students had been able to accomplish all criteria of recount text, such as using mostly material processes which deals with ideational metafunction, using correct tense and subject to fulfil the mood exists in interpersonal metafunction, and using reiteration and zigzag pattern as representation of textual metafunction. However, since there was problem to overcome, a strategy was proposed known as â€œPOWERâ€ which stands for Plan, Organise, Write, Edit, and Revise, which is hoped to help students developed a well-constructed text fulfilling all sine qua non attributes that recount text has.